There Is No Hierarchy of Norms, There Is a Hierarchy of Instances: Normative and Subject-Political Justification of the Hierarchy of Normative Legal Acts in the Teachings of Hans Kelsen and Karl Schmitt - Anton D. Ukhanov (RUDN Journal of Political Science, 2023)
The problem of legal force and the hierarchy of normative legal acts must be considered at the intersection of political and legal knowledge, since such acts are not just a form of external consolidation of legal norms prescribing a certain model of behavior to the subject, but also express the state-power will, fix the institutional and political framework and the alignment of political forces in society. In the history of political and legal thought, two main ways of substantiating the legal force of normative legal acts have taken shape: normative and subject-political. The most consistently and argumentatively indicated methods are set out in the theoretical works of German lawyers of the last century, Hans Kelsen and Karl Schmitt. The article proposes to compare the views of thinkers on the nature of legal force and the hierarchy of normative legal acts. In the final part of the work, a variant of a conciliatory interpretation of competing approaches is substantiated, and conclusions are drawn about the relative practical significance of the analyzed theoretical models in the context of legal practice and the political process.